Local fauna of bumblebees (Hymenoptera, Apidae) in the lower reaches of the Northern Dvina River - Potapov, GS; Kolosova, YuS (Arctic Environmental Research, 2019)
This article is devoted to an investigation of the local fauna of bumblebees in the lower reaches of the Northern Dvina River in northern Russia where 27 species of bumblebees were found during the present study. The basis of the local fauna of bumblebees in the lower reaches of the Northern Dvina River is related to species with a wide range. The majority of the species are Transpalaearctic. Holarctic, Sub-Transpalaearctic, whereas West-Central Palaearctic are less represented. According to the latitudinal aspect the majority of the species are temperate, and the rest are boreal and arcto-temperate. One of species found in the local fauna is subboreal. The number of species in the studied local fauna is the largest among the local faunae of the northern part of the Arkhangelsk Region. It is comparable to the local faunae of the southern part of this region. Here is recorded species such as Bombus soroeensis, B. distinguedus, B. ruderarius, B. veteranus, B. humilis, and others, which are not typical of native taiga habitats but are the meadow species in the European North of Russia. Due to the wide development of meadows and ruderal communities in the lower reaches of the Northern Dvina River, these species are widely represented here. The rare species in the studied local fauna are B. patagiatus, B. humilis, B. consobrinus, and B. schrencki.